Effects of micro financing towards agriculture entrepreneur / Nor Kartini Muhammad - Muhammad, Nor Kartini (2011)
This study attempts to determine the effects of Micro Financing. The objective of this research is to identify the relationship between Micro Financing and productivity, income and subsidy. The researcher had distributed the questionnaire among 100 agriculture entrepreneurs in Kodiang, Kedah. In this study interpreted the data and findings by using the tables, graph and also figures. Besides, there are three analysis method in SPSS are been used to analyze the data, which is frequency distribution, reliability analysis and simple regression analysis. Thus, the findings from the SPSS show that two of the independent variables (income and productivity) have significant relationship with the effects of Micro Financing. Other variable (subsidy) show that no significant relationship with micro financing. The researcher also used AMOS to analyze the data. The findings from the AMOS program show only income have a significant relationship with micro financing. The others variable show that no significant with micro financing